2012
DOI: 10.7589/0090-3558-48.3.676
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of White-Tailed Deer (Odocoileus Virginianus) to Experimental Infection With Epizootic Hemorrhagic Disease Virus Serotype 7

Abstract: ABSTRACT:During the fall of 2006, in Israel, epizootic hemorrhagic disease virus (EHDV) serotype 7 caused an intense and widespread epizootic in domestic cattle that resulted in significant economic losses for the dairy industry. The susceptibility of potential North American vector and ruminant hosts to infection with EHDV-7 is not known but is essential to understanding the potential for establishment of this exotic orbivirus in North America if it were introduced. Our primary objective was to determine whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…29 WTD have now been experimentally infected with 4 (1, 2, 6, 7) of the 7 provisional EHDV serotypes, and clinical disease has been replicated or induced with each. 17,54,61 It is reasonable to speculate that this species is susceptible to clinical disease with all EHDV serotypes, although variation in susceptibility likely occurs among WTD subspecies. 21 Furthermore, confirmed fatal BT infections (natural or experimental) in WTD have been documented with multiple serotypes of BTV (1,3,8,10,11,12,13,17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…29 WTD have now been experimentally infected with 4 (1, 2, 6, 7) of the 7 provisional EHDV serotypes, and clinical disease has been replicated or induced with each. 17,54,61 It is reasonable to speculate that this species is susceptible to clinical disease with all EHDV serotypes, although variation in susceptibility likely occurs among WTD subspecies. 21 Furthermore, confirmed fatal BT infections (natural or experimental) in WTD have been documented with multiple serotypes of BTV (1,3,8,10,11,12,13,17).…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study, EHDV-2 was isolated from 75% (87 of 116) of midges at 4 to 14 dpf, and 36% (42 of 116) of midges had virus titers !10 2.7 TCID 50 /midge. 54 The apparently variable susceptibility of C. sonorensis to infection with different EHDV serotypes is interesting and has not been investigated. Previous studies of BTV infection in field and laboratory populations of C. sonorensis describe heterogeneity in response to oral infection among BTV serotypes, 32,33 although mechanisms of such variation remain unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An isolate of EHDV-7 from the 2006 outbreak in Israel was shown to be infectious but not to cause clinical disease in cattle (Eschbaumer et al, 2012). A similar study demonstrated that an EHDV-7 Israel isolate caused clinical disease in US white-tailed deer (Ruder et al, 2012a). This discrepancy is not surprising because in general white-tailed deer are more susceptible to EHDV than cattle, especially under experimental infection conditions.…”
Section: Introductionmentioning
confidence: 69%
“…An emerging serotype in North America, EHDV-6, is detected regularly during EHD outbreaks and in surveillance samples from white-tailed deer (Wildlife Management Institute 2012). There is increased concern that the geographic distribution of EHDV-6 in North America may be changing and that there is a potential for other EHDV serotype to emerge (Ruder et al 2012). Therefore, it is critical to continue monitoring the distribution of endemic EHDV serotypes.…”
mentioning
confidence: 99%